Watershed Sustainability Index for Langat UNESCO HELP River Basin, Malaysia - Elfithri, Rahmah; Mokhtar, Mazlin; Pauzi Abdullah, Mat; Raihan Taha, Mohd; Ekhwan Toriman, Mohd; Mohamad Yasin, Ruhizan; Yaakub, Jasni; Puteri Khairani Khirotdin, Rd; Mahathir Amir Sultan, Mohamad; S.A, Ishak; N.M, Ramzan; Khairul Amri Kamarudin, Mohd; et al. (International Journal of Engineering and Technology, 2018)
The study on Watershed Sustainability Index (WSI) has been conducted to analyst the environmental condition in the area incorporating ecological baseline and socio-economic conditions. WSI is an integrated indicator based on basin Hydrology, Environment, Life and Policy (HELP) state condition. It is suitable to be applied in the Langat River Basin in Malaysia which has similar catchment area (up to 2,350 km2) and is one of the UNESCO HELP River Basin since 2004. The WSI analysis which uses a pressureâ€“stateâ€“response function based on basin HELP Indicator was done for Langat River Basin by using relevant available 5 years data for the period of 2009 to 2013. It is found that Langat River Basin is having WSI value of 0.68 which falls under the category of medium sustainability (between 0.5-0.8). Based on the maximum value (i.e. 1) or high sustainability (i.e. WSI value more than 0.8) it can be said that Langat is in the good side in term of sustainability. Few management aspects need to be improved and maintained well to be more sustainable. The assessment provides Langat River Basin with more information that is crucial in managing the basin through the adoption of UNESCOâ€™s HELP Framework.Â Â Â